A textile platform using continuous aligned and textured composite microfibers to engineer tendon-to-bone interface gradient scaffolds - Calejo, Isabel (2019)
Tendon-to-bone interfaces exhibit a hierarchical multitissue transition. To replicate the progression from mineralized to nonmineralized tissue, a novel 3D fibrous scaffold is fabricated with spatial control over mineral distribution and cellular alignment. For this purpose, wet-spun continuous microfibers are produced using polycaprolactone (PCL)/ gelatin and PCL/gelatin/hydroxyapatite nano-to-microparticles (HAp). Higher extrusion rates result in aligned PCL/gelatin microfibers while, in the case of PCL/gelatin/HAp, the presence of minerals leads to a less organized structure. Biological performance using human adipose-derived stem cells (hASCs) demonstrates that topography of PCL/gelatin microfibers can induce cytoskeleton elongation, resembling native tenogenic organization. Matrix mineralization on PCL/gelatin/HAp wet-spun composite microfibers suggests the production of an osteogenic-like matrix, without external addition of osteogenic medium supplementation. As proof of concept, a 3D gradient structure is produced by assembling PCL/gelatin and PCL/gelatin/HAp microfibers, resulting in a fibrous scaffold with a continuous topographical and compositional gradient. Overall, the feasibility of wet-spinning for the generation of continuously aligned and textured microfibers is demonstrated, which can be further assembled into more complex 3D gradient structures to mimic characteristic features of tendon-to-bone interfaces.